Physical Quality of Magelang Duck’s Egg Fed Diet Containing Indigofera sp. and Lemuru Fish Oil - Arif Darmawan; . Sumiati; Widya Hermana (Buletin Ilmu Makanan Ternak, 2016)
The aim of this study was to study the effect of Indigofera sp. leaf meal and lemuru fish oil in rations on physical quality of Magelang duck’s egg. One hundred and eighty laying duks of 22 weeks old were randomly divided into 6 experimental units with 3 replications. The experimental design used was a factorial completely randomized design 3 x 2, the first factor was levels of Indigofera sp. leaf meal (0%, 5.5% and 11%) and the second factor was levels of lemuru fish oil (0% and 2%).  Parameters observed were egg weight, percentage of albumen weight, percentage of yolk weight, percentage of egg shell weight, egg shell thickness and yolk color. The result showed that the use 11 % of Indigofera sp. leaf meal or  2% of lemuru fish oil  increased  significantly (P<0.01) percentage of albumen weight and yolk color,  and reduced significantly (P>0.05) egg weight and  percentage of yolk weight.  The treatments had no significant effect (P> 0.05) on  percentage of egg shell weight and egg shell thickness.